Rancang Bangun Generator Thermal Dengan Pemanfaatan Limbah Panas Knalpot Motor Replika - AlHidayat, ALHidayat; Bakhri, Syaiful; Dinata, Seflahir (Majalah Ilmiah Teknologi Elektro; Vol 20 No 1 (2021): (Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2021.v20i01.P08, 2021)
Abstract— Thermoelectric power plants are solid state devices that provide direct energy conversion from thermal energy due to a temperature gradient into electrical energy based on the "Seebeck effect", working by converting heat energy into electricity directly. In "Design of Thermal Generator with the Utilization of Heat Exhaust from Motor Replica". The test uses 4, TEP1-142 T300 in series, the test is carried out in several stages, namely no-load testing, the highest voltage obtained reaches 8 volts at (?T) the temperature difference between TH and TL 31 oC, the temperature is TH 65 oC and the temperature TL 34 oC. then using a load of 5 watt led lights experiencing a voltage drop, the maximum voltage is 5 volts with the power obtained 0.41 watts at 0.07 amperes, the test uses a boost converter, the voltage is as stable as 5 volts, where the thermoelectric voltage is V-in. must get a voltage of 3 volts. In this test the thermoelectric generator generates electrical power which is influenced by the temperature difference between TH and TL where the TL temperature must be lower than TH to get high power, the temperature at TL must always be maintained, therefore a good temperature cooling radiator is needed at TL, which is not more than 40 oC, the power generated can only turn on a 5volt lamp with a power of 0.34 watts which is very small because the number of thermoelectric modules also affects the power produced, the advantage in this test is that we can take advantage of the exhaust heat of motorized vehicles.